An abundant family of methylated repetitive sequences dominates the genome of Physarum polycephalum. - Peoples, O P (1983)
A significant portion (20%) of the Physarum genome can be isolated as a HpaII-resistant, methylated fraction. Cloned DNA probes containing highly-repeated sequences derived from this fraction were used to define the pattern of structural organisation of homologous repeats in Physarum genomic DNA. It is shown that the probes detect an abundant, methylated family of sequences with an estimated genomic repetition frequency greater than 2100, derived from a large repeated element whose length exceeds 5.8kb. Sequences comprising the long repetitive element dominate the HpaII-resistant compartment and account for between 4-20% of the Physarum genome. Detailed restriction/hybridisation analysis of cloned DNA segments derived from this compartment shows that HpaII/MspI restriction sites within some copies of the long repeated sequence are probably deleted by mutation. Additionally, segments of the repeat are often found in different organisational patterns that represent scrambled versions of its basic structure, and which are presumed to have arisen as a result of recombinational rearrangement in situ in the Physarum genome. Preliminary experiments indicate that the sequences are transcribed and that the structural properties of the repeat bear some resemblance to those of transposable genetic elements defined in other eukaryotic species.